1994
DOI: 10.1007/bf02015016
|View full text |Cite
|
Sign up to set email alerts
|

Urine interleukin-6 and interleukin-8 in children with acute pyelonephritis, in relation to DMSA scintigraphy in the acute phase and at 1-year follow-up

Abstract: The relationship between urine interleukin-6 (IL-6) and interleukin-8 (IL-8)/creatinine quotients and 99mTc-dimercaptosuccinic acid (DMSA) scintigraphy, performed within 10 days of acute first-time pyelonephritis and after 1 year, was studied in 41 children. The urine IL-6 and IL-8/creatinine quotients were also related to the urine N-acetyl-beta-D-glucosaminidase (NAG) and albumin/creatinine quotients. Presence of DMSA uptake defects, reflecting local inflammation, in children in the acute phase of pyelonephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 22 publications
1
32
0
1
Order By: Relevance
“…The development of scars in early life, particularly in patients with VUR, has been correlated with the development of hypertension, pre-eclampsia, renal insufficiency, and end-stage renal disease. Tullus et al showed that the initial IL-6 level in urine of children with pyelonephritis correlated with DMSA uptake defects in the acute phase as well as 1 year later (35). These data suggest that modulating the inflammatory response in patients with UTI should decrease the development of renal scars and the sequelae associated with them.…”
Section: Discussionmentioning
confidence: 98%
“…The development of scars in early life, particularly in patients with VUR, has been correlated with the development of hypertension, pre-eclampsia, renal insufficiency, and end-stage renal disease. Tullus et al showed that the initial IL-6 level in urine of children with pyelonephritis correlated with DMSA uptake defects in the acute phase as well as 1 year later (35). These data suggest that modulating the inflammatory response in patients with UTI should decrease the development of renal scars and the sequelae associated with them.…”
Section: Discussionmentioning
confidence: 98%
“…Normal uptake in a segment was given the value 0, and decreased uptake was graded 1-3. From the size and degree of a defect in DMSA uptake, a DMSA score was calculated (20).…”
Section: Patientsmentioning
confidence: 99%
“…Tullus (24) ve Krzemiẻn (21) çalışmalarında, DMSA'da skarı olanların idrar IL-8 düzeyinin olmayanlardan farklı olmadığını bildirilmiştir. Gökçe ve ark.…”
Section: Discussionunclassified